PERAN PEREMPUAN DALAM PENCEGAHAN KORUPSI DI INDONESIA (Pengabdian Masyarakat Pada PKK Kelurahan Wonorejo Karanganyar) - Supriyanta, Dora Kusumastuti & (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2017)
The high level of corruption in Indonesia raises an effort to fight. Efforts to prevent corruption can be prevented through families by increasing the role of women. The purpose of community service awareness raises women in the household in an effort to prevent corruption. Methods implemented by methods of socialization, counseling, and training. The result of devotion is the prevention of corruption can be done in the family through the role of women, as mothers, women as wives and women as working women.Conclusion by maximizing the role of women will be able to increase corruption prevention efforts in Indonesia.Key Word: women, corruption ,prevention